2020
DOI: 10.1371/journal.pone.0235663
|View full text |Cite
|
Sign up to set email alerts
|

Inexpensive, non-invasive biomarkers predict Alzheimer transition using machine learning analysis of the Alzheimer’s Disease Neuroimaging (ADNI) database

Abstract: The Alzheimer's Disease Neuroimaging (ADNI) database is an expansive undertaking by government, academia, and industry to pool resources and data on subjects at various stage of symptomatic severity due to Alzheimer's disease. As expected, magnetic resonance imaging is a major component of the project. Full brain images are obtained at every 6-month visit. A range of cognitive tests studying executive function and memory are employed less frequently. Two blood draws (baseline, 6 months) provide samples to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 38 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…We found that the predictability of changes in cognitive test scores was low, leaving a large portion of variance unexplained. Our results complement previous works which show good discrimination of progressing and non-progressing subjects [ 16 , 21 ] in cohorts comprising both A β -positive and A β -negative subjects. In particular, we show that discriminating between subjects who are potential candidates for drugs designed to reverse or slow down A β plaque formation presents a harder prediction task.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the predictability of changes in cognitive test scores was low, leaving a large portion of variance unexplained. Our results complement previous works which show good discrimination of progressing and non-progressing subjects [ 16 , 21 ] in cohorts comprising both A β -positive and A β -negative subjects. In particular, we show that discriminating between subjects who are potential candidates for drugs designed to reverse or slow down A β plaque formation presents a harder prediction task.…”
Section: Discussionsupporting
confidence: 90%
“…Most predictive models of neurodegenerative diseases are based on recent advances in machine learning (ML) models by obtaining data sets with measurements of cognition and neuropathology from large cohorts [ 16 , 20 22 ]. In this context, classification methods such as random forest [ 13 , 21 , 23 , 24 ] and logistic regression (LR) [ 21 , 25 27 ] have been used to predict whether individuals will decline or remain stable in their diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…A neural network model based on data from 1737 participants in the ADNI database was effective in predicting AD progression in a separate set of 110 participants who were CN or had MCI at baseline [ 14 ]. Other machine learning-based models have employed neuroimaging and noninvasive methods using blood biomarkers to predict AD progression [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The predictive models of neurodegenerative diseases are based on recent advances in machine learning (ML) models by obtaining data sets with measurements of cognition and neuropathology from large cohorts [24,25,20,26]. In this context, most ML models focused on binary classification methods predicting with high accuracy whether individuals diagnosed with MCI will decline or remain stable in their diagnosis [27].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, most ML models focused on binary classification methods predicting with high accuracy whether individuals diagnosed with MCI will decline or remain stable in their diagnosis [27]. The classification techniques such as random forest [15,28,29,25], logistic regression (LR) [30,31,32,25] and support vector machines (SVM) [33,29] have been used. Most previous AD studies based on ML focus on predicting conversion between the CN, MCI and AD diagnosis [20,34] based on diagnosis classification using various neuroimaging tech-niques such as magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%